Bringing Sanctuary to School: Assessing School Climate as a Foundation for Culturally Responsive Trauma-Informed Approaches for Urban Schools. (January 2020) - Blitz, Lisa V.; Yull, Denise; Clauhs, Matthew
Decades of federal economic policies that have concentrated poverty into isolated communities have devastated urban education, and expose youth and families to high stress and trauma. Disproportionately negative outcomes for students of color and those who are economically disadvantaged can be understood as manifestations of negative racial school climate and inadequate responsiveness to students' trauma. As part of a school–university partnership to inform culturally responsive trauma-informed pedagogy, this study assessed the climate of a racially diverse high-poverty elementary school. Findings explored the application of the trauma-informed Sanctuary Model to address students' trauma and a social justice response for urban education.